Lectotypification of Peruvian Melastomataceae described by Cogniaux from Weberbauer collections - Burke, Janelle M; Michelangeli, Fabian (Phytotaxa, 2013)
We provide a comprehensive reference for lectotypifications of Peruvian Melastomataceae taxa described by Cogniaux in 1908 from Weberbauer specimens at Berlin. Of the 45 taxa described from the Cogniaux publication, we designate new lectotypes for 39 taxa: Axinaea nitida, Axinaea tetragona, Blakea villosa, Brachyotum asperum, Centradeniastrum roseum, Calyptrella robusta, Graffenrieda foliosa, Macrocentrum fasciculatum var. peruvianum, Miconia alpina, Miconia atrofusca, Miconia brevistylis, Miconia chrysanthera, Miconia crassistigma, Miconia densifolia, Miconia dumetosa, Miconia falcata, Miconia floccosa, Miconia fruticulosa, Miconia glutinosa, Miconia grisea, Miconia hamata, Miconia lugubris, Miconia monzoniensis, Miconia neriifolia var. brevifolia, Miconia nigricans, Miconia secundifolia, Miconia setinervia, Miconia urbaniana, Miconia weberbaueri, Myrmidone peruviana, Tibouchina asperifolia, Tibouchina brevisepala, Tibouchina calycina, Tibouchina calycina var. parvifolia, Tibouchina cymosa, Tibouchina laevis, Tibouchina rhynchantherifolia, Tibouchina virescens, and Tibouchina weberbaueri.